Online businesses see rapid growth since MCO last year - UMP, PNC (2021)
KUALA LUMPUR, Jan 15 — While it is no secret that the small and medium enterprise (SME) sector has been badly impacted by the Covid-19 pandemic and subsequent enforcement of movement restrictions since last March, many SMEs managed to keep afloat by taking their businesses online.